Nonmonogamy: Changing Intimacy and Sociological Research - Lyzenko, Darja (Sociologija. Mintis ir veiksmas, 2018)
[full article and abstract in Lithuanian; abstract in English]This article discusses the concepts of monogamy, nonmonogamy and consensual nonmonogamy (swinging, polyamory and open relationships). The cultural forces questioning the perspectives of the normativity of monogamy are similarly being argued. In addition, issues regarding the mono-normative position of monogamy, its legitimacy and relationship with the concepts of monogamy and nonmonogamy are also explored.
Keywords: monogamy, nonmonogamy, swinging, polyamory, intimacy, mononormativity